TANGGUNG JAWAB INDUK PERUSAHAAN DALAM PERUSAHAAN KELOMPOK - Harini, Putu; Dewi Kasih, Desak Putu (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 02, Januari 2015)
This paper is about legal relationship between the parent company with subsidiaries in the corporate liability group and the parent company of the legal actions undertaken by a subsidiary to a third party within the company group. Problems occurred that provision parent company as an independent entity that can take responsibility in the engagement undertaken by the subsidiary has not been clearly and carefully regulated. So that raises a question of law if the third party losses. This paper aims to understand and know about the legal relationship between the parent company with subsidiaries in a corporate group, and to know the responsibility of the parent company against legal actions undertaken in the subsidiary companies of the group. This paper method produces using the normative with the descriptive nature of the research. This paper presented a study that the legal relationship between the parent company with subsidiaries in the group company is a contractual legal relationship between the parent company as the majority shareholder of the subsidiary so that the parent company can control the running of the company with majority ownership of shares. And the parent company can be held accountable for the actions of its subsidiary law (defaults) it can be shown that the interference of the parent company to the subsidiary business.
Keywords: Relations Law, Responsibility, Parent Company